PELAKSANAAN PENDAFTARAN TANAH SISTEMATIS LENGKAP DALAM MEMBERIKAN KEPASTIAN HUKUM HAK ATAS TANAH MASYARAKAT (DI KOTA PEKANBARU) - Warman, Kurnia; Putra, Ardiansyah; Elvardi, Jean (Universitas Ekasakti, 2023)
PTSL is a land registration activity for the first time that is carried out simultaneously for all land registration objects throughout the territory of the Republic of Indonesia in one village/kelurahan area or other name equivalent to that, which includes the collection of physical data and juridical data regarding one or several registration objects. Land for registration purposes. In this study, the data sources were obtained from library research and field research. Data collection techniques were carried out through structured interviews and document studies. The results of the research on PTSL constraints in Pekanbaru City are the high cost of having to pay the payable PPh and BPHTB taxes, the problem of rights used, human resources, the problem of absentee land/land that is far from the owner and the problem of announcing physical data and juridical data. While the efforts made by the Pekanbaru City Land Office in overcoming PTSL obstacles are strengthening quality control over each stage of PTSL, providing work maps (base maps, land registration maps, area maps, SPIPP maps, and Regional Government/BUMN/BUMD asset data) to officers in the field, providing punishment and a whistleblowing system mechanism, improving data validation procedures for KKP applications, reviewing and improving PTSL budget implementation guidelines and quality control.